The contribution of FTO rs9939609 and RETN rs1862513 polymorphisms in predisposing resettled indigenous (Orang Asli) Temiar to metabolic syndrome - Nur Sakinah Harun; Azizul Fadzli Wan Jusoh; Mohd Adzim Khalili Rohin; Rosliza Yahaya; Nik Ahmad Shaifuddin Nik Him; Mohd Nizam Zahary (Egyptian Journal of Medical Human Genetics, 2023)
Abstract Purpose Metabolic syndrome (MetS) is characterized by visceral obesity, elevated blood pressure and fasting blood glucose, increased triglycerides, and lower high-density lipoprotein cholesterol. MetS related with intricate gene-environment interactions. FTO and RETN variants were linked to the occurrence of MetS, but inconsistent results were reported. Therefore, this study was conducted to evaluate the potential role of FTO rs9939609 and RETN rs1862513 polymorphisms and their susceptibility risk to MetS among resettled indigenous or Orang Asli (OA) of Temiar subtribe under resettlement scheme by the Malaysia government. Methods A cross sectional study was performed involving 123 Temiar volunteers located in Gua Musang, Kelantan. MetS was identified using modified NCEP-ATP III. DNA extraction was done using peripheral blood. Polymerase Chain Reaction–Restriction Fragment Length Polymorphism (PCR–RFLP) was employed to genotype FTO rs9939609 and RETN rs1862513 polymorphisms. Susceptibility risk of the polymorphisms (FTO rs9939609 and RETN rs1862513) with MetS was determined by binary logistic regression analysis and odds ratios (ORs). Results FTO rs9939609 and RETN rs1862513 were associated with risk of MetS susceptibility among the Temiar subtribe with estimated OR 19.9 (P < 0.001) and 20.7 (P = 0.006) for heterozygous (T/A) and homozygous (A/A) genotype at FTO rs9939609 locus, respectively; OR 222.5 (P < 0.001) and 26.2 (P = 0.005) for heterozygous (C/G) and homozygous (G/G) genotype at RETN rs1862513 locus, respectively. Conclusion The genetic polymorphisms of FTO rs9939609 and RETN rs1862513 were associated with the risk of MetS among the Temiar subtribe. The findings contribute toward the fundamental prevention plan to decrease the probability of MetS development.